(untitled) (Research, Society and Development, 2022)
A high-risk pregnancy is one in which the life or health of the mother and/or the fetus and/or the newborn are more likely to be affected. Given the lack of referral flow and proper supervised care for high-risk pregnant women, there is a need to explore the progress of triage of care for such patients in tertiary services. This study aimed to carry out a careful analysis of the care provided at Hospital Guilherme Álvaro (HGA) to pregnant women referred to high-risk care. In this study, the population base of high-risk prenatal screening visits at Hospital Guilherme Álvaro (HGA) was used, in which the clinical conditions of pregnant women referred in the period 2020 and 2021 were evaluated. From the epidemiological analysis of pregnant women referred to high risk screening at Hospital Guilherme Álvaro, it was possible to highlight that 41.4% were between 26 and 35 years of age; and were between 20-32 weeks of gestational age. Regarding the main risk pathologies, there is a proportion of 23.5% of patients with arterial hypertension and 26.1% of gestational diabetes, thus being the main responsible for hospital admissions. Studies of this nature come with the aim of knowing the range of risk factors for pregnancy, as well as the main cities that need more monitoring, generating more qualified care for pregnant women and fetuses.